Haiti: Strategy to Alleviate the Pressure of Fuel Demand on National Woodfuel Resource - World Bank; Ministry of Environment, Republic of Haiti (World Bank, Washington, DC, 2014)
Haiti suffers from a serious deterioration of its natural environment and, in particular, from a heavy pressure on its natural resources. The reasons for this deterioration are multiple (poverty level, demographic pressure, agricultural techniques and insecurity regarding land tenure) and, therefore, go beyond the strict scope of energy. However, the wood-fuel consumption is one of the main factors of this deterioration. On a national scale, about 70 percent of the energy needs are met using firewood and charcoal. Although the local wood-fuel resources have been overexploited for more than 20 years, the price of wood-fuels does not reflect this scarcity phenomenon which constitutes a serious ecological threat at the countrywide level. The household energy sector remains, by far, the main consumer of wood-fuels, in as much as it absorbs 70 percent of the overall supply. However, this sector is characterized by very low efficiency in terms of use outputs.